Implementasi Pengelolaan Dana Kampung (Studi Kasus di Kampung Asey Besar Distrik Sentani Timur) - Lampung, Jasrinaldo; Safkaur, Otniel; Paru, Sara (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2024)
This research aims to analyze the implementation of Village Fund management based on Minister of Home Affairs Regulation Number 20 of 2018. This research is a qualitative descriptive research. The data analysis method used in this research is case study research, which is an appropriate strategy to use in research that uses how or why as the main research question, the researcher has little time to control the events being studied, and the focus of the research is contemporary phenomena, to track contemporary events. The results obtained from this research are, Based on the research results described above, it can be concluded that.”Implementation of Village Fund Management in Asey Besar Village from the activity planning stage to final accountability refers to Permendagri Number 20 of 2018 concerning provisions for Village financial management. At the planning stage for village financial management, the Asey Besar village government held village deliberations to determine the Village Revenue and Expenditure Budget (APBK), involving community participation in providing input in the form of suggestions or opinions relating to planned activities to be carried out.